Advanced maternal age and adverse pregnancy outcomes: A cohort study - M. Guarga Montori; A. Álvarez Martínez; C. Luna Álvarez; N. Abadía Cuchí; P. Mateo Alcalá; S. Ruiz-Martínez (Elsevier, 2021)
Objectives: To assess the association between advanced maternal age and adverse perinatal outcomes in single pregnancies. Materials and methods: A cohort study was conducted using data from 27,455 singleton births attended at our hospital between 2007 and 2018. Three maternal age groups were established, and perinatal outcomes were compared between-groups (<35 years (n = 19,429; 70.7%), 35-40 years (n = 7189; 26.2%), and >40 years (n = 846; 3.1%). The data were compared using chi-square analysis and the results were adjusted using a logistic regression model. Decision trees were designed to examine the fetal mortality and caesarean section variables. We used the SPSS 23 statistical software program for the statistical analysis. Results: The mean age of the women was 31.21 years. No differences were found associated with age for neonatal acidosis, an Apgar score <7 at 5 min after birth, threatened preterm labour, preterm rupture of membranes, or high-grade perineal tear. The analyses found statistically significant increases in the rates of hypertensive disorders, diabetes mellitus, induction of labour, and caesarean section, after 35 years of age. The risks of fetal death, neonatal admission, small for gestational age, placenta previa, instrument delivery, maternal ICU admission, and postpartum haemorrhage were greater after 40 years of age. Conclusions: The results of our study indicated that women >35 years of age had worse perinatal outcomes, compared with younger women. This finding was more evident in patients >40 years of age, which highlighted the greater risk of fetal death and serious maternal complications in this group.